2009
DOI: 10.1007/s12199-009-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between daily physical activity and neighborhood environments

Abstract: The results to this study demonstrate that daily PA was high among female subjects living in a NE with land use mix-diversity, and who had an awareness of places to walk to and the accessibility to facilities for daily necessities in their neighborhood. For male subjects, daily PA was high among those who perceived the aesthetics of and accessibility to facilities for pleasure in their neighborhood. Further research is needed to determine the association between PA and NE on the basis of sex differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 23 publications
1
60
1
Order By: Relevance
“…In the ANEWS, NE is focusing on the influence of the NE on residents and does not include the location of the workplace. Neighborhood was defined as the area within an approximately 10-min walking distance from a residence, and seven NE characteristics were assessed: density of dwelling (degree of density of residential buildings), proximity to service facilities (land use mix with nonresidential service facilities, such as restaurants, works and retail stores), number of service facilities within a 10-min walk (land use mix-access), street connectivity (intersection is short and easy to cross, and few dead end streets), places for walking (sidewalks on most of the streets and are separated from the traffic road), good view (trees along the streets or natural scenery while walking), and traffic and crime safety [17,24,25]. Reliability and internal consistency of the Japanese version of the ANEWS were tested and were shown to be moderate to high [17,25].…”
Section: Perceived Neighborhood Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In the ANEWS, NE is focusing on the influence of the NE on residents and does not include the location of the workplace. Neighborhood was defined as the area within an approximately 10-min walking distance from a residence, and seven NE characteristics were assessed: density of dwelling (degree of density of residential buildings), proximity to service facilities (land use mix with nonresidential service facilities, such as restaurants, works and retail stores), number of service facilities within a 10-min walk (land use mix-access), street connectivity (intersection is short and easy to cross, and few dead end streets), places for walking (sidewalks on most of the streets and are separated from the traffic road), good view (trees along the streets or natural scenery while walking), and traffic and crime safety [17,24,25]. Reliability and internal consistency of the Japanese version of the ANEWS were tested and were shown to be moderate to high [17,25].…”
Section: Perceived Neighborhood Environmentmentioning
confidence: 99%
“…First, questions regarding WT did not distinguish purpose-specific walking, e.g., for transportation or for leisure. Previous studies reported that street connectivity was related to walking for transportation while a good view was related to walking for exercise [17]. However, because of the difficulty in distinguishing purpose-specific WT in daily life, WT, which included all kinds of walking such as commuting, shopping, and leisure, was queried to help induce more accurate recall.…”
Section: After Adjustment For Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several empirical studies have shown associations between green space and level of physical activity (Hoehner et al, 2005;Björk et al, 2008;Panter and Jones, 2008;Kondo et al, 2009;Prins et al, 2009;Coombes et al, 2010). There is also growing evidence suggesting that perceived environmental attributes may capture health promoting aspects that objective measures do not capture (McCormack et al, 2008;Leslie et al, 2010), and that neighborhood perceptions might stronger correlate with physical activity behavior than objective assessments (Prins et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the seven studies [63][64][65][66][67][68][69] that examined both walking and cycling for transport, two studies [65,69] found inconsistent results. Christiansen and colleagues [69] conducted an international comparative study, and they found that intersection density was linearly positively related to cycling for transport, but not linearly related to walking for transport.…”
Section: Comparison Of Results Between Walking and Cycling For Transportmentioning
confidence: 99%